2019
DOI: 10.1111/bju.14655
|View full text |Cite
|
Sign up to set email alerts
|

An updated approach to incremental nerve sparing for robot‐assisted radical prostatectomy

Abstract: A.M. and S.C. contributed equally to this work ObjectivesTo update the algorithm for performing incremental nerve sparing (NS) using our multiparametric magnetic resonance imaging (mpMRI)-based nomogram. Patients and methodsWe applied the coefficients of the nomogram to the observations extracted from our population of patients who underwent robot-assisted radical prostatectomy between February 2014 and October 2015 and who received preoperative mpMRI. The information considered were PSA level, highest side-sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…Though we strongly feel that pathological confirmation is a diagnostic gold standard and should be recommended in all instances prior to surgery, an RP in these patients may be considered. Finally, advances in robotic nerve-sparing RP have led to improved functional outcomes while maintaining oncological control in properly selected patients 16. However, despite the reduced morbidity of these techniques, surgery is never without risk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Though we strongly feel that pathological confirmation is a diagnostic gold standard and should be recommended in all instances prior to surgery, an RP in these patients may be considered. Finally, advances in robotic nerve-sparing RP have led to improved functional outcomes while maintaining oncological control in properly selected patients 16. However, despite the reduced morbidity of these techniques, surgery is never without risk.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, advances in robotic nerve-sparing RP have led to improved functional outcomes while maintaining oncological control in properly selected patients. 16 However, despite the reduced morbidity of these techniques, surgery is never without risk. Regardless of the surgical technique and degree of nerve sparing, RP carries the risk of significant consequences, both functional (eg, incontinence, erectile dysfunction) and perioperative (eg, deep-vein thrombosis, pulmonary embolism, myocardial infection).…”
Section: Discussionmentioning
confidence: 99%
“…53,54 Martini et al reported an algorithm for carrying out graded nerve-sparing procedures using their own nomogram. 55,56 The nomogram consisted of several parameters; that is, preoperative PSA values, Gleason biopsy grade, maximum percentage of tumor in the biopsy core with the highest Gleason score and the findings of extracapsular extension defined by multiparametric magnetic resonance imaging. 55,56 The patients were divided into four risk groups; that is, low-, intermediate-, high-and very high-risk groups, based on the probability values of side-specific extracapsular extension of the prostate calculated by the aforementioned nomogram.…”
Section: Transrectal Ultrasonographymentioning
confidence: 99%
“…55,56 The patients were divided into four risk groups; that is, low-, intermediate-, high-and very high-risk groups, based on the probability values of side-specific extracapsular extension of the prostate calculated by the aforementioned nomogram. 55,56 They suggested that graded nerve-sparing procedures should be carried out according to this risk grouping.…”
Section: Transrectal Ultrasonographymentioning
confidence: 99%
See 1 more Smart Citation